A contribution for a pragmatics-based approach to concurrent engineering implementation - Popović, Nenad (Strojniški vestnik, 2013)
The paper investigates how a pragmatics-based approach may influence Concurrent Engineering (CE) implementation projects. Pragmatics, a field of semiotics, is used as a perspective for analyzing, as an instrument for constructing manufacturing systems and, in this particular research, as an instrument for CE implementation projects. In particular, as a part of the CE implementation methodology, modeling and the effects of different interpretations (as pragmatics aspects) of the assessment of processes simultaneity in a manufacturing organization are studied. The underlying thesis is that different interpretations significantly influence the perception of the organizations reality, which has an impact on the projects success. As a representation class, the so-called Simultaneity (Concurrency) Matrix (SCM) was used for simultaneity process assessment. The thesis is validated in two manufacturing companies. The results suggest that further improvements of the CE implementation methodologies, when using the pragmatics-based approach, lead to better quality of decisions and provide some assurance for the success of short-time and low-cost CE implementation projects.
Keywords: concurrent engineering; concurrent engineering implementation; matrika sočasnosti (SCM); pragmatics; pragmatika; simultaneity; simultaneity assessment; sočasno inženirstvo; uvajanje sočasnega inženirstva; vrednotenje sočasnosti